DAMPAK PELAYARAN KAPAL LAUT DI ALUR SUNGAI MUSI - Sugeng, Sunarso (Gema Teknologi, 2010)
Sunarso Sugeng, in this paper explain that the effect of movement of ship in Musi River cause environmental damage in the form of path exterior erosion / wall step aside river,effect from this material erosion result the happening of accelerateing sedimentation which enough quickly so that degrade energy support sea transport path and for the conservancy of groove this sea transport require dredging fund which do not lessen fastly of this sedimentation one of the way of is to make regulation demarcation speed of sea transport to ship have certain dimension .. To lessen erosion effect movement of other causes and boat, earn is also considered to regarding strong effort of bank groove by protecting it with bagwark, revetment etcetera as according to principle engineer river Key word Sungai musi